The journal editor: Friend or foe?. Issue 2 (June 2015) - Hall, Jenny; Hundley, Vanora; van Teijlingen, Edwin
Abstract The role of the journal editor may not be well known by authors. The purpose of this article is to explain the role in order to encourage future participation in reviewing and publication. Illustration is provided of the publishing process.